Analysis of the Sustainability, Vulnerability, and Challenges of Aquaculture Livelihood Projects - Berio, Mark Jason M.; Salugsugan, John Clifford P (Technium Business and Management, 2022)
Background: Aquaculture is the best source of sustainable livelihood for communities, as long as the technology is in place and environment friendly. The aquaculture in southern Negros Occidental continues to experience a crisis that includes this recent COVID-19 pandemic, in addition to rapid financial and structural changes and awareness of farming’s enormous influence on ecosystem health. Oyster and fish cages farmers were familiar with and associated terms such as environmental protection, small-scale aquaculture, profitability, and productivity with sustainable oyster and fish production. Furthermore, the researcher, who has experience in the aquaculture industry, desires to investigate sustainability and recognizes this aquaculture owners/operators’ vulnerability and challenges in their livelihood. Thus, the paper analyzed the sustainability, vulnerability, and challenges of aquaculture livelihood projects in Southern Negros. Methods: Using a descriptive quantitative research design, 50 aquaculture operators/owners answered a checklist questionnaire to analyze the sustainability, vulnerability, and challenges of aquaculture livelihood projects. Frequency count and percentage distribution were used in analyzing the quantitative data. Results: In human capital, the operators/owners have at least a high school graduate to engage in aquaculture livelihood and range 0-1 year of experience. They are aware of health and safety practices, and the skills they know are feeding and harvesting. They are sole workers, and the physical skill they perform is swimming. For natural capital, all operators/owners gained access to the Nanunga River permit from the Local Government Unit of Municipality of Hinigaran. The size of the fishing ground and fish pens is at 5x5meters, and they conduct monthly coastal cleaning for the maintenance of the surroundings. The timeline and growth and water sensitivity affect the timeline growth of the oyster shell and fish species, respectively. They are also given an action plan to prepare the climate change and initiate the monthly coastal cleanup to maintain cleanliness in the coastal. In terms of financial capital, the income of operators/owners is higher compared to expenses, debt, and taxes paid per harvest. As a result, they can set aside a net amount for savings. Also, they received support from the government every year. They were given a three-year projected financial statement to know the income, expenses, debt, savings, and taxes. Regarding social capital, the aquaculture livelihood helps their community by providing livelihood to their families, providing food supplies, and contributing to economic gain. The operators/owners are trusted, and they follow norms in the community. They are also involved in the monthly meetings to discuss the concerns about their aquaculture livelihood projects. They also avail of the financial assistance loan from the government through the Department of Labor and Employment (DOLE) Pangkabuhayan Program. These imply scheduling a mandatory monthly meeting for the Aquaculture owners/operators, which is also open to the community. In physical capital, most operators/owners have fish pen infrastructure, fish boats, materials for oyster farming, and fish cage fishing. They also used electricity and fuel as a source of energy. They sent an application for financial aid to the Department of Labor and Employment (DOLE) to purchase new materials for Aquaculture. The major vulnerabilities are the Covid-19 pandemic, climate change, oil spills, seasonality, and technological changes. The major challenges that the Aquaculture operators/owners face are lack of knowledge, high/low tide, no preparation of unforeseen expenses, lack of participation among members in monthly association meetings, and cannot afford to purchase new materials for fish pens and fishing boats. Overall, the findings in the light of the Department for International Development (DFID) Sustainable Livelihood Framework, the results were validated as aquaculture livelihood projects are sustainable in terms of human, natural, financial, social, and physical capital. Conclusion: The aquaculture livelihood projects of aquaculture growers in Southern Negros were sustainable in terms of human, natural, financial, social, and physical capital. It shows that the aquaculture operators/owners have various knowledge and skills in the industry, preservation of water resources and cleanliness of coastal areas, more income and less expenses and debts growers, improve the economy and the people’s standard of living and relationships and more fish pens infrastructure and increase of supplies of materials. Notwithstanding the existing vulnerabilities and challenges, the aquaculture livelihood projects were manageable and could easily cope with unforeseen events. Practical Value of the Paper: The local government agency may explore the possibility of assisting aquaculture livelihood projects in gathering information for periodic evaluation and monitoring of the financial status of aquaculture livelihood projects for reporting purposes. It is hoped that future researchers utilize this study as the basis for further research, especially studies focusing on the sustainability, vulnerability, and challenges of other livelihoods like agriculture industries. Also, the Aquaculture owners/operators can use the strategic plan to present to the Department of Labor and Employment (DOLE) and other organizations to avail the financial assistance and funding in the future.